Impacts on manufacturing workers as part of a whole-system energy transition - Ciez, Rebecca E. (Frontiers in Sustainable Energy Policy, 2023)
Providing access to good employment opportunities has become a key area of focus to ensure a just energy transition and to ensure that there is sufficient support for the technology transitions necessary for deep decarbonization. However, a societal transition to a decarbonized energy system will impact workers beyond those involved in energy resource extraction and energy production. Workers involved in manufacturing, especially those working in manufacturing industries that are energy and emissions intensive may face additional changes as those industries undergo technological changes. While discussions of the quality of jobs have focused on things like compensation, employment terms, and representation, other job dimensions, like the intrinsic characteristics of the work, health and safety, and work-life balance, stand to be directly impacted by technology change and are largely excluded from consideration. As these new technologies are developed and new energy sources are introduced to support manufacturing, we should also consider sociotechnical solutions that balance worker quality of life amongst other considerations like the utilization of new capital resources. Incorporating considerations across a wider definition of job quality dimensions will help to ensure that there is a sufficient workforce available to meet the demands of a decarbonization transition.